2000
DOI: 10.1051/apido:2000120
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric diversity of Apis cerana Fabr. within the Philippines

Abstract: counterpart, A. mellifera L., the understanding of its taxonomy and biology is only in the beginning. Early taxonomists like Maa [11] had split up the eastern cavitynesting bees into 11 species and several subspecies. Based on groups generated by Abstract -The diversity of Apis cerana Fabr. in the Philippines was studied using morphometric methods. A total of 101 samples of A. cerana from feral and hived colonies, and foragers were collected throughout the Philippine archipelago. The 39 morphometric characters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
5

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 9 publications
2
18
0
5
Order By: Relevance
“…As such, collection times varied, with some samples several years older than the rest. These samples were examined earlier using morphometric techniques [26], and more recently using DNA sequencing techniques [27]. Philippine A. cerana are from the following locations (see Fig.…”
Section: Collectionsmentioning
confidence: 99%
“…As such, collection times varied, with some samples several years older than the rest. These samples were examined earlier using morphometric techniques [26], and more recently using DNA sequencing techniques [27]. Philippine A. cerana are from the following locations (see Fig.…”
Section: Collectionsmentioning
confidence: 99%
“…Recently, the utilization of geometric morphometrics has increased in population (Tilde et al 2000, Francoy et al 2006, Nunes et al 2008, Nunes et al 2012, heritability (Monteiro et al 2002), evolutionary (Bonatti et al 2014) and reproductive (Carvalho et al 2011) studies of bees. These reports have shown that geometric morphometric data are effective in the identification of groups and lineages (Francoy et al 2008, Francoy et al 2009, Bischoff et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, multivariate morphometric analyses of the former lag behind the latter and a recent survey of the literature shows that infraspecific classification and population structure in Apis cerana are fraught with difficulties (Hepburn et al, 2001). A beginning toward a resolution of this disparity is apparent from the recent publication of several such analyses for different parts of Asia (Sasaki, 1994;Deowanish et al, 1996;Damus and Otis, 1997;Sylvester et al, 1998;Sihanuntavong et al, 1999;de la Rúa et al, 2000;Smith et al, 2000;Tilde et al, 2000).…”
Section: Introductionmentioning
confidence: 99%